2017
DOI: 10.7554/elife.29702
|View full text |Cite
|
Sign up to set email alerts
|

Many si/shRNAs can kill cancer cells by targeting multiple survival genes through an off-target mechanism

Abstract: Over 80% of multiple-tested siRNAs and shRNAs targeting CD95 or CD95 ligand (CD95L) induce a form of cell death characterized by simultaneous activation of multiple cell death pathways preferentially killing transformed and cancer stem cells. We now show these si/shRNAs kill cancer cells through canonical RNAi by targeting the 3’UTR of critical survival genes in a unique form of off-target effect we call DISE (death induced by survival gene elimination). Drosha and Dicer-deficient cells, devoid of most miRNAs,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
174
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(193 citation statements)
references
References 80 publications
17
174
1
Order By: Relevance
“…When transfecting siCAG/CUG into various human (Fig B) and mouse (Fig C) cancer cell lines at 10 nM, all cancer cells stopped growing within hours of transfection and eventually most of the cells died with no outgrowth of recovering cells (Supplementary Movies EV1, EV2, EV3, EV4, EV5, EV6, EV7, EV8, EV9 and EV10; Appendix Fig S1A). All cancer cells transfected with siCAG/CUG showed morphological changes similar to the ones we observed in cells undergoing DISE (Appendix Fig S1B, ). We found that siCAG/CUG killed HCT116 cells even when transfected at 10 pM (Fig D).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…When transfecting siCAG/CUG into various human (Fig B) and mouse (Fig C) cancer cell lines at 10 nM, all cancer cells stopped growing within hours of transfection and eventually most of the cells died with no outgrowth of recovering cells (Supplementary Movies EV1, EV2, EV3, EV4, EV5, EV6, EV7, EV8, EV9 and EV10; Appendix Fig S1A). All cancer cells transfected with siCAG/CUG showed morphological changes similar to the ones we observed in cells undergoing DISE (Appendix Fig S1B, ). We found that siCAG/CUG killed HCT116 cells even when transfected at 10 pM (Fig D).…”
Section: Resultssupporting
confidence: 75%
“…Similar to cells undergoing DISE, when transfected with siCAG/CUG, ~1,800 critical survival genes but not ~400 nonsurvival control genes were significantly enriched in the downregulated genes in cells transfected with siCAG/CUG but not with siCGA/UCG in a gene set enrichment analysis (Fig D). In fact, we detected a ~12‐fold increased percentage of survival genes compared to the nonsurvival genes among the downregulated RNAs in the siCAG/CUG‐treated cells (Fig E)—a higher difference than seen in cells treated with DISE‐inducing sh‐ or siRNAs (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Six AngII shRNAs were designed according to the sequences of Genebank database and protocols from previous studies in order to select the two optimal sequences [15]. In brief, the expression vector was purchased from System Biosciences (Mountain View, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of Alu-repeats in human lincRNA-p21 [12] suggests that this change was due in part to hybridization of Alu-repeats in human lincRNA-p21 that target mRNAs through partial complementarity (Figure 2D). Although our microarray and RNA-seq analysis after siRNA transfection showed that the abundance of complementary target mRNAs changes, we cannot rule out an offtarget effect of siRNAs contributing to miRNA abundance, non-specifically [21]. It is also possible that the interaction between CCAACC DNA sequence and nuclear lincRNA-p21 could affect transcription of target mRNAs.…”
Section: Discussionmentioning
confidence: 99%